IMPLEMENTASI SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT GIGI MENGGUNAKAN METODE TEOREMA BAYES - Fadhila Anggraini; Nur Hikmah; herry wahyono (Fakultas Teknik Unkris Jakarta, 2022)
Teeth are one of the most vital organs of the human body, therefore maintaining dental health is very important. The reason why people only do dental check-ups when their teeth are sick and the lack of public awareness of themselves about dental health and the long queues that cause crowds at the dental clinic are the reasons why people are reluctant to come to the dental clinic during the pandemic which is still in existence in Indonesia. Therefore we need a system to facilitate both the handling and prevention of early symptoms of dental disease that can be done online. The method used in this study is the Bayes theorem method, where this method can calculate how often the symptoms appear. The results of the research on the implementation of an expert system for diagnosing dental disease is a website-based application that can help identify dental diseases with a percentage of 80%